Sterile Inflammation in Drosophila. (8th April 2015) - Shaukat, Zeeshan; Liu, Dawei; Gregory, Stephen
Abstract : The study of immune responses in Drosophila has already yielded significant results with impacts on our understanding of vertebrate immunity, such as the characterization of the Toll receptor. Several recent papers have focused on the humoral response to damage signals rather than pathogens, particularly damage signals from tumour-like tissues generated by loss of cell polarity or chromosomal instability. Both the triggers that generate this sterile inflammation and the systemic and local effects of it are only just beginning to be characterized in Drosophila . Here we review the molecular mechanisms that are known that give rise to the recruitment of Drosophila phagocytes, called hemocytes, as well as the signals, such as TNF α, that stimulated hemocytes emit at sites of perceived damage. The signalling consequences of inflammation, such as the activation of JNK, and the potential for modifying this response are also discussed.